Mature dendritic cells correlate with favorable immune infiltrate and improved prognosis in ovarian carcinoma patients - Truxova, Iva; Kasikova, Lenka; Hensler, Michal; Skapa, Petr; Laco, Jan; Pecen, Ladislav; Belicova, Lucie; Praznovec, Ivan; Halaska, Michael J; Brtnicky, Tomas; Salkova, Eva; Rob, Lukas; et al. (Journal for immunotherapy of cancer, 2018)
A high density of tumor-infiltrating CD8+ T cells and CD20+ B cells correlates with prolonged survival in patients with a wide variety of human cancers, including high-grade serous ovarian carcinoma (HGSC). However, the potential impact of mature dendritic cells (DCs) in shaping the immune contexture of HGSC, their role in the establishment of T cell-dependent antitumor immunity, and their potential prognostic value for HGSC patients remain unclear. We harnessed immunohistochemical tests and biomolecular analyses to demonstrate that a high density of tumor-infiltrating DC-LAMP+ DCs is robustly associated with an immune contexture characterized by TH1 polarization and cytotoxic activity. We showed that both mature DCs and CD20+ B cells play a critical role in the generation of a clinically-favorable cytotoxic immune response in HGSC microenvironment. In line with this notion, robust tumor infiltration by both DC-LAMP+ DCs and CD20+ B cells was associated with most favorable overall survival in two independent cohorts of chemotherapy-naïve HGSC patients. Our findings suggest that the presence of mature, DC-LAMP+ DCs in the tumor microenvironment may represent a novel, powerful prognostic biomarker for HGSC patients that reflects the activation of clinically-relevant anticancer immunity.
Keywords: dospělí; Kaplan-Meier Estimate; nádory vaječníků; tumor infiltrující lymfocyty; Female; biologické markery; Biomarkers; Adult; ženské pohlaví; Kaplanův-Meierův odhad; Dendritic Cells; dendritické buňky; Lymphocytes, Tumor-Infiltrating; nádorové mikroprostředí; Immunohistochemistry; lidé; staging nádorů; Ovarian Neoplasms; Aged, 80 and over; Carcinoma; karcinom; imunohistochemie; Immunophenotyping; prognóza; imunofenotypizace; T-lymfocyty - podskupiny; proporcionální rizikové modely; Aged; Proportional Hazards Models; Prognosis; lidé středního věku; Tumor Microenvironment; senioři nad 80 let; senioři; T-Lymphocyte Subsets; Middle Aged; Neoplasm Staging; Humans